Glandular trichomes that mediate resistance to green peach aphid in tomato genotypes from the cross between S. galapagense and S. lycopersicum (Acta Scientiarum. Agronomy, 2019)
The aim of this study was to verify the resistance of tomato genotypes (crossed with Solanum galapagense) to the green peach aphid, Myzus persicae, and the association of this resistance with glandular trichomes. Leaf trichomes were quantified for seven F2 genotypes of the BPX-486 population derived from crossing S. lycopersicum ‘TOM-684’ and S. galapagense accession ‘LA-1401’, for the commercial controls ‘TOM-584’ and ‘Santa Clara’, and for the accession ‘LA-1401’. After this evaluation, the genotypes were subjected to two nonpreference resistance tests of the green peach aphid in the laboratory, one with choice and the other without choice. Five genotypes (BPX-486-17, BPX-486-62, BPX-486-10, BPX-486-46, and BPX-486-08) and the accession LA-1401 exhibited a high density of type IV glandular trichomes and a lower mean number of nymphs and adults of M. persicae than two genotypes (BPX-486-313 and BPX-486-383) and the controls with a low density of glandular trichomes, in all the evaluations of both tests. Significant negative correlations between the density of type IV glandular trichomes of the tomato genotypes and the preference of M. persicae were found, which confirms the association between this type of glandular trichome and resistance to M. persicae in tomato genotypes.